Moderating effect of income on the service environment and customers’ behavioral intention - Haque, A. K. M. Ahasanul; Hashim, Nurhazirah; Hasim, Nur Hasyimah (Elsevier, 2015)
The property industry acts as vital sector whereby the service environment directly correlates the customers’ behavioral intention in purchasing a property. However, to date, a study regarding service environment and its impact still not fully addressed in the property industry. Thus, the purpose of this study is to investigate the relationship between service environment and customers’ behavioral intention moderated by income in Malaysian property industry. A total of 357 respondents were participated in this study by using a convenience sampling. The result shown that lower middle income was significantly moderated the relationship between service environment and customers’ behavioral intention